PRINSIP-PRINSIP PENANGANAN KEMISKINAN DI MADINAH PADA MASA NABI MUHAMMAD SAW - Arif Chasanul Muna (Jurnal Hukum Islam, 2011)
This article endeavors to observe our prophet PBUH’s efforts in alleviating the poverty in Madina after his hijrah. The relevance compilations of hadiths (sayings and doings of the prophet PBUH) are described as historical sources to see the methods and the means of the prophet PBUH in eradicating the poverty. These hadiths are explained not only to be interpreted literally, but contextually. In doing so, this writing would be started by depicting the city of Madina with its economic activities and poverty’s problem that emerged after the hijrah. The response and the manner of the prophet PBUH in alleviating the poverty will be explaining afterward.